Evaluation on Short-Term Therapeutic Effect of 2 Porphyrin Photosensitizer-Mediated Photodynamic Therapy for Esophageal Cancer - Liu, Huilong (Technol Cancer Res Treat, 2019)
PURPOSE: To analyze and study the short-term therapeutic effects and main adverse effects of 2 Porphyrin photosensitizer-mediated photodynamic therapy for esophageal cancer. METHODS: We apply the hematoporphyrin derivative and hematoporphyrin injection produced by different manufacturers at different periods as photosensitizers in therapy of 79 esophageal cancer cases, with the administration dosage of 5 mg/kg and intravenous drip 24 hours before irradiation. We apply the gold vapor laser and semiconductor laser, respectively, as treatment light source, with the power density of 100 to 300 mW/cm(2) and energy density of 100 to 300 J/cm(2). After treatment for 1 to 4 sessions, we evaluate the short-term therapeutic effects as complete response, partial response, minor response, or no change, and then make comparative study on therapeutic effects and adverse effects. RESULTS: There were 47 patients in hematoporphyrin derivative group, including 3 (6.4%) patients with complete response, 31 (66.0%) patients with partial response, 10 (21.3%) patients with minor response, and 3 (6.4%) patients with no change. The dysphagia score was reduced from 2.53 (1.16) before treatment to 1.32 (1.20; P < .01) after treatment. There were 32 patients in the hematoporphyrin injection group, including 3 (9.4%) patients with complete response, 19 (59.4%) patients with partial response, 6 (18.8%) patients with minor response, and 4 (12.5%) patients with no change. The dysphagia score was reduced from 2.41 (1.13) before treatment to 1.18 (0.99; P < .01) after treatment. The dysphagia scores of 2 groups after treatment were significantly reduced compared to those before treatment. Both groups did not display serious adverse effect. CONCLUSIONS: Two porphyrin photosensitizers in treatment of esophageal cancer at different clinical stages all had good effect with similar therapeutic effect, mild adverse effect, and good tolerance, which implies it is a preferable palliative therapy means.